Comparison of Satellite-retrieved NO2 Vertical Column Density with Ground-level NO2 concentration in a provincial scale region. Issue 1 (December 2020) - Zheng, Fengbin; Xia, Yu; Ge, Qiang; Cai, Kun
Abstract: Satellite remote sensing will have certain errors in data retrieval accuracy, which requires further ground observation verification. This paper examines and verifies 2019 Jiangsu provincial Ground-level monitoring data and TROPOMI data to evaluate the applicability of TROPOMI tropospheric NO2 Vertical Column Density (VCD) data and compares the results to OMI data analysis verification results. The results show that the correlation coefficient r between the TROPOMI NO2 data and Ground-level monitoring data at the monthly mean scale is as high as 0.9, and consistent seasonal cyclic changes are observed. The correlation between Ground-level monitoring data and OMI NO2 data is lower than TROPOMI (r=0.78 < 0.9). Compared to OMI satellites, the TROPOMI attains a smaller deviation in tropospheric NO2 monitoring. Jiangsu Province had the highest monthly average concentration in January, which were 38.67 ug/m 3 (Ground-level), 17.35 × 10 15 molec/cm 2 (TROPOMI) and 20.04 × 10 15 molec/cm 2 (OMI). The lowest concentration in August was 13.39 ug/m 3 (Ground-level), 5.2 × 10 15 molec/cm 2 (TROPOMI) and 7.03 × 10 15 molec/cm 2 (OMI).